2012
DOI: 10.1002/job.1827
|View full text |Cite
|
Sign up to set email alerts
|

Environmental standards and labor productivity: Understanding the mechanisms that sustain sustainability

Abstract: Summary In the last decade, a rising number of firms have adopted voluntary international environmental management and product standards, such as the international ISO 14001 management standard or organic certification. Although emerging research analyzes the impact of these standards on environmental and financial performance, there is to our knowledge no empirical research on how they affect the productivity of employees. In this paper, we investigate the direct relationship between environmental standards a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
206
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(230 citation statements)
references
References 136 publications
(187 reference statements)
17
206
0
7
Order By: Relevance
“…He concluded that green organization would require to use learning in association with environment and sustainability as an intrinsic and continuous part of the social responsibility process. In other words, training and development are essential elements in the implementation of green management (Delmas & Pekovic, 2013). Training and developmental processes are appropriate mechanisms to facilitate corporate sustainability and pro-environmental practices, which in turn can create an opportunity to develop intellectual capital (Olusanya, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…He concluded that green organization would require to use learning in association with environment and sustainability as an intrinsic and continuous part of the social responsibility process. In other words, training and development are essential elements in the implementation of green management (Delmas & Pekovic, 2013). Training and developmental processes are appropriate mechanisms to facilitate corporate sustainability and pro-environmental practices, which in turn can create an opportunity to develop intellectual capital (Olusanya, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Correa et al (2013) stated that many firms may use green human recourse management, have benefited from their implementation, their employees have a better morale and green organizations have better financial performance. Any adoption of environmental standards helps firms profit from reducing their negative environmental effect by improving their labor productivity (Delmas & Pekovic, 2013). Now, according to these expression and also the importance of this issue in the oil industry, we need to investigate the barriers on green human resources management in the industry, and this article aims to identify barriers of implementing green human resources management in Iran's oil industry.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies using data for French firms and employees find that, for firms that have adopted voluntary environmental standards, employees are more likely to work uncompensated overtime hours [4], labor productivity is higher [7], and difficulties with recruitment are smaller [8]. Nevertheless, when we look at these issues at an aggregated level, it is not easy to see through all the identification and interpretation problems that they present to the researcher.…”
Section: Type Of Organization Definition Sourcementioning
confidence: 99%
“…Ainsi, Toyota a annoncé en 2007 que les absences des employés sur son site de Torrance (CA customer service) ont été réduites de 14 % après qu'ils aient étaient transférés dans des bâtiments écologiques (Carlton, 2007). De même, Delmas et Pekovic (2013) …”
Section: Répondre Aux Attentes Des Employésunclassified